Persistent diurnal enuresis in a 6-year-old boy after bilateral ureteroneocystostomy - Szawłoga, Tomasz; Orzechowska, Aleksandra; Sobieszczańska-Droździel, Aleksandra (Journal of Education, Health and Sport, 2023)
Urinary incontinence is one of the most common symptoms in children and adolescents. Due to numerous causes, a thorough examination is necessary. We present a case of a 6-year-old boy with diurnal enuresis, who was admitted to our Department for further treatment after the procedure of bilateral ureteroneocystostomy due to suspected bilateral ureter stenosis. With the persistence of the incontinence, our examination revealed a posterior urethral valve which was incised and the symptoms subsided.